2010
DOI: 10.1063/1.3319751
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative electron attachment in nonplanar chlorocarbons with π∗/σ∗-coupled molecular orbitals

Abstract: Total absolute cross sections for the dissociative electron attachment (DEA) process are reported for a series of nonplanar ethylenic and phenylic compounds monosubstituted with (CH(2))(n)Cl groups, where n=1-4. Coupling between the local pi* molecular orbitals provided by the unsaturated moieties and the sigma* (C-Cl) orbital is thus examined as a function of the separation of these groups. In particular, the coupling is viewed from the perspective of the interacting temporary negative ions formed by short li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
(24 reference statements)
3
15
0
Order By: Relevance
“…The LUMO + 3 corresponds to a σ * (a ) molecular orbital and is concentrated on the C-N bond. We also computed the canonical eigenvalues of the Fock operator and, using the empirical scaling relations for the LUMO (π * ) and LUMO + 1 (σ * ) orbitals from [35], we found for the LUMO and for the LUMO + 3, the values 0.39 and 4.60 eV for the vertical attachment energies (VAE), respectively, which are close to the present calculated π * and σ * resonance positions. We also computed the σ * VAE using another scaling relation from [36] for the LUMO, and obtained 4.61 eV.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The LUMO + 3 corresponds to a σ * (a ) molecular orbital and is concentrated on the C-N bond. We also computed the canonical eigenvalues of the Fock operator and, using the empirical scaling relations for the LUMO (π * ) and LUMO + 1 (σ * ) orbitals from [35], we found for the LUMO and for the LUMO + 3, the values 0.39 and 4.60 eV for the vertical attachment energies (VAE), respectively, which are close to the present calculated π * and σ * resonance positions. We also computed the σ * VAE using another scaling relation from [36] for the LUMO, and obtained 4.61 eV.…”
Section: Resultssupporting
confidence: 77%
“…Besides, the results obtained from the scaling relations of Refs. [35,36] suggest that the present calculations have located the σ * resonance at the right position. At the fixed nuclei approximation, there is no evidence of a σ * resonance at 2.4 eV.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Experience with many systems has also shown that the VOs of a closed shell neutral molecule describe the orderings and symmetries of low-lying shape resonances. [30][31][32][33][34][35][36] This is also true for the ordering of the ROHF states of the corresponding doublet openshell ions that are accessible.…”
Section: Selection Of Qbssmentioning
confidence: 84%
“…The theoretical explanation of the phenomenon may be based on the dependence of the cross-section for dissociative capture on the energy of electrons. The maximum cross-section for benzyl chloride is at about 0.8 eV [ 30 , 31 ]. This energy value is higher than the energy of electrons in nitrogen under the electric field in the IMS detector.…”
Section: Resultsmentioning
confidence: 99%